Spirituality and ethical identity of muslim teachers beyond competence - Dimyati Sajari; Romlah Abubakar Askar; Abdul Rosyid; Harapandi Dahri (ATTARBIYAH: Journal of Islamic Culture and Education, 2026)
Contemporary discussions on teacher professionalism are largely dominated by competence-based paradigms emphasizing technical skills, performance indicators, and measurable outcomes. Such approaches, while necessary, often marginalize the ethical and spiritual dimensions that sustain the moral integrity of teaching. Within Islamic educational thought, teaching is traditionally understood as a moral and spiritual vocation rather than a technical profession. This study examines the role of spirituality in shaping the ethical identity of Muslim teachers beyond competence-oriented frameworks. Employing a qualitative conceptual approach based on normative–philosophical analysis, this research synthesizes classical Islamic educational texts and contemporary scholarly literature on teacher ethics and spirituality. The findings reveal four interrelated dimensions that constitute ethical identity: spiritual intentionality (niyyah), moral exemplarity (uswah) grounded in adab, spiritual self- regulation, and service-oriented professionalism (khidmah and raḥmah). These dimensions form an integrated framework in which spirituality functions as a foundational orientation rather than a supplementary attribute. The study argues that pedagogical competence is ethically insufficient without spiritual grounding and offers a conceptual framework for teacher formation that integrates ethical integrity, resilience, and moral responsibility in contemporary educational contexts.